2012
DOI: 10.1111/j.1742-4658.2012.08707.x
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium binding and kinetic characterization of putative tetracycline repressor family transcription regulator Fad35R from Mycobacterium tuberculosis

Abstract: Fatty acids play critical role in the survival and virulence of Mycobacterium tuberculosis (Mtb). Activation of fatty acids by acyl-CoA synthetases (Fad) into fatty acyl-CoA is the first and one of the crucial steps in fatty acid metabolism. Mtb possesses 36 fatty acyl-CoA synthetases, unlike Escherichia coli, which has single enzyme. However, the mechanisms by which the expression of these multiple Fad genes is regulated remain uncharacterized. We characterized the DNA-and ligand-binding properties of a putat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 53 publications
1
18
0
Order By: Relevance
“…The average number of binding sites for TFs with a motif was 246 (range 14–859), compared with an average of 28 peaks (range 3–437) for those TFs where a significant consensus motif could not be identified. For TFs with previously characterized DNA-binding motifs, this analysis corresponded well with previous reports (for example, Rv2506 (refs 37 , 38 ), Rv2359 (ref. 39 ), DosR (ref.…”
Section: Resultssupporting
confidence: 88%
“…The average number of binding sites for TFs with a motif was 246 (range 14–859), compared with an average of 28 peaks (range 3–437) for those TFs where a significant consensus motif could not be identified. For TFs with previously characterized DNA-binding motifs, this analysis corresponded well with previous reports (for example, Rv2506 (refs 37 , 38 ), Rv2359 (ref. 39 ), DosR (ref.…”
Section: Resultssupporting
confidence: 88%
“…Comparison of sequence topology maps of 48 structures of TFRs identified by Yu et al (18) indicate that 13 contain at least two of the three conserved basic residues in orientations permissive to CoA binding. Of note, Fad35R of M. tuberculosis (PDB code 4G12) regulates the expression of fad35, which encodes an acetyl-CoA synthetase involved in fatty acid degradation (41). Although Fad35R binds tetracycline, other evidence suggested that a fatty acyl-CoA could be the physiological effector (41).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, Fad35R of M. tuberculosis (PDB code 4G12) regulates the expression of fad35, which encodes an acetyl-CoA synthetase involved in fatty acid degradation (41). Although Fad35R binds tetracycline, other evidence suggested that a fatty acyl-CoA could be the physiological effector (41). The presence of Lys-184 on the ␣8-␣9 loop, Arg-166 on the apical end of helix ␣8, and His-170 in the middle of helix ␣8 supports this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…While writing this manuscript, a paper was published describing a single motif in the intergenic region of bkaR_fadD35 in M. tuberculosis. Binding was demonstrated to this region together with affinity measurements, and it was shown that both tetracycline and palmityl-coA could interfere with binding (Anand et al, 2012). These authors suggested that bkaR (which they call fad35R and consider to be a homologue of E. coli FadR) controls the expression of fadD35 in M. tuberculosis.…”
Section: Discussionmentioning
confidence: 99%